AB0181 ASSOCIATION BETWEEN SINGLE NUCLEOTIDE POLYMORPHISMS (SNPS) OF THE BAFF GENE AND FATIGUE IN PRIMARY SJöGREN'S SYNDROME. (June 2019) - Flessa, Christina Maria; Nezos, Adrianos; Zampeli, Evangelia; Moutsopoulos, Haralampos M.; Mavragani, Clio
Abstract : Background: Primary Sjögren's Syndrome (SS) is characterized by B lymphocyte hyperactivity with B cell activating factor (BAFF) acting as an important regulator. Single Nucleotide Polymorphisms (SNPs) of the BAFF gene have been implicated in the pathogenesis of several autoimmune diseases including lupus and SS both of which are characterized by heightened fatigue levels, often compromising quality of life. Objectives: To explore potential associations between several BAFF gene SNPs and fatigue status experienced by primary SS patients. Methods: Fatigue status was assessed by Functional Assessment of Chronic Illness Therapy–Fatigue (FACIT-F) scale in 178 primary SS patients. Five SNPs (rs9514827, rs1041569, rs9514828, rs1224141, rs12583006) of the BAFF gene were tested in DNA extracted from peripheral blood of all patients enrolled in the study using the RFLP-PCR method. A cut-off value of <30 was used, which indicates severe fatigue. Analysis of BAFF SNPs in association with fatigue levels was performed by the online platform SNPStats. Results: The frequency of T/T genotype of both rs9514828 and rs1224141 was reduced in primary SS patients with severe fatigue compared to those without (17.9% vs 36.7%, p=0.0094 and 51.8 vs 69.2%, p=0.027, respectively. The corresponding ORs [95%CI] in the dominant model were 0.38 [0.17-0.82] and 0.48 [0.25-0.92], respectively. No statistically significant associations between fatigue status and other SNPs tested were detected. Conclusion: We report novel associations between genetic makeup and primary SS-associated fatigue with the rs9514828 and rs1224141 BAFF T/T genotypes decreasing the likelihood of fatigue development among these patients. These findings need to be validated in multi-center studies. References: [1] Mavragani, C.P. and H.M. Moutsopoulos, Sjogren's syndrome. Annu Rev Pathol, 2014. 9: p.273-85. [2] Koçer, B., Tezcan, M. E., Batur, H. Z., Haznedaroğlu, Ş., Göker, B., İrkeç, C. and Çetinkaya, R., Cognition, depression, fatigue, and quality of life in primary Sjögren's syndrome: correlations. Brain and Behavior, 2016. 6: p.1–11. [3] Karageorgas, T., et al., Fatigue in Primary Sjogren's Syndrome: Clinical, Laboratory, Psychometric, and Biologic Associations. Arthritis Care Res (Hoboken), 2016. 68(1): p. 123-31. [4] Norheim, K.B., et al., A possible genetic association with chronic fatigue in primary Sjogren's syndrome: a candidate gene study. Rheumatol Int, 2014. 34(2): p.191-7. Acknowledgement: This research is co-financed by Greece and the European Union (European Social Fund-ESF) through the Operational Programme «Human Resources Development, Education and Lifelong Learning» in the context of the project "Strengthening Human Resources Research Potential via Doctorate Research" (MIS-5000432), implemented by the State Scholarships Foundation (ΙκΥ). Disclosure of Interests: Christina Maria Flessa: None declared, Adrianos Nezos: None declared, Evangelia Zampeli Speakers bureau: Roshe, Astrazeneca, Haralampos M. Moutsopoulos: None declared, Clio Mavragani: None declared